(untitled) (Nexus International Journal of Science and Education, 2024)
This study explored the influence of school policies on student behavior and academic performance. I get down the features and streaks of the existing issues in policies and disciplinary practices, their effectiveness, and the teacher's coping practices on the challenges that come along the way. To achieve the study's objectives, I used phenomenology, and 10 participants of this study were from Tacunan Elementary School, Tugbok District, Davao City Division. The study disclosed different themes for teachers' experiences, such as cultural relevance, parent involvement, and teacher buy-in, of which these factors in policies that were relevant to the cultural and social context of the school community were more likely to be effective. Schools that consider their students' unique needs and experiences are better equipped to develop policies that resonate with them. Another theme was Coping with the challenges of collecting results. Sub-themes were Lack of Clarity, Resistance from Teachers, and Unintended Consequences; these coping mechanisms were Policies that were not communicated or understood by students, teachers, and parents and may not be influential in shaping behavior and performance. Policies need to be communicated clearly and consistently. Building trust and acknowledging the possible effect of employee trust on organizational commitment was crucial. Moreover, The Insights were drawn from the study's findings on the challenges in their role in school policies and disciplinary practices and the emergence of the two themes: building relationships and communication and seeking support and collaboration.